2020
DOI: 10.3390/land9120497
|View full text |Cite
|
Sign up to set email alerts
|

Renewables—To Build or Not? Czech Approach to Impact Assessment of Renewable Energy Sources with an Emphasis on Municipality Perspective

Abstract: The process of decarbonization and increasing the share of renewable sources of energy (RES) arising not only from European Union targets leads to development, expansion, and construction of new RES. Municipalities thus face a decision whether to support/accept RES projects or not. Although energy managers are part of the municipality management in almost all bigger cities, mayors of smaller municipalities have to go through the decision-making process on their own. The aim of the paper is to present a newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…A more specific metric is Bird mortality, that resembles Biodiversity but refers only to the number of birds that were killed with the implementation and operation of the power plant. Land use can be described as the reduction in the quality and quantity of the resources that the land can give [6] or as the income generated by leasing or selling the land for the construction of the plant [27].…”
Section: Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…A more specific metric is Bird mortality, that resembles Biodiversity but refers only to the number of birds that were killed with the implementation and operation of the power plant. Land use can be described as the reduction in the quality and quantity of the resources that the land can give [6] or as the income generated by leasing or selling the land for the construction of the plant [27].…”
Section: Environmental Impactmentioning
confidence: 99%
“…Air pollution is another metric that assess the air quality after the implementation of renewable energy [7], [11], [13], [27].…”
Section: Environmental Impactmentioning
confidence: 99%
“…Innovations in the solar sector have also reduced the global average selling prices of solar PV. The anticipated new and more advanced technologies and increased manufacturing of PV installations will allow for a stabilization of the capital costs at lower levels [33,34].…”
Section: Czech Republicmentioning
confidence: 99%
“…If only focused on solar energy, the PV plants need to expand from the current capacity of 2.25 GW to 3.8 GW, including closing older solar photovoltaic power plants [16]. An exciting observation revealed that mayors of different regions could play a significant role in bridging the gap between renewable energy projects in the Czech areas [17]. According to NECP, Czech Republic has set a lower target for itself with an RES proportion of 22% by 2030.…”
Section: The Czech Republicmentioning
confidence: 99%